Psychometric properties of the Ukrainian version of the vocational identity status assessment (VISA-19) - AKKAYA, Kateryna; OLEFIR, Valeriy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Vocational identity is considered one of the most important domains of overall identity, and its study is gaining increasing relevance and popularity among Ukrainian researchers. An especially crucial aspect of the research on vocational identity is the study of its development. However, we have identified a lack of Ukrainian methods for researching vocational identity development. This study is dedicated to translating and adapting the English-language Vocational Identity Status Assessment (VISA) questionnaire and examining its psychometric properties and measurement invariance for Ukrainian students.Methods. In a cross-sectional study, 458 students from various specialties in their 1st to 5th years participated (62% were female), aged 17 to 22 years (M = 19). The North American Vocational Identity Status Assessment (VISA) questionnaire, developed by Porfeli et al. (2011), was used for translation. Two translators performed both forward and backward translations, and the translated version was presented to the participants via Google Forms. A confirmatory factor analysis was conducted to assess the questionnaire's factor structure, validity, reliability, and measurement invariance.Results. The shortened version of the questionnaire (VISA-19) was accepted as the primary version, demonstrating the six-factor original structure and good psychometric properties: CFI = 0,954, TLI = 0,943, RMSEA = 0.067[0,060-0,075], SRMR = 0,053, a ranges from 0,69 to 0,81, CR from 0,65 to 0,77, AVE from 0,43 to 0,59, HTMT from 0,057 to 0,856. Metric, scalar, and strict measurement invariance by gender for the shortened version of the questionnaire was established, with ACFI ranging from -0,004 to 0,000, ARMSEA from -0,001 to 0,003, and ASRMR from 0,001 to 0,005.Conclusions. The Ukrainian shortened version of the VISA-19 questionnaire exhibited good psychometric properties and measurement invariance by gender and can be utilized for further research and practical applications.
Keywords: identity; vocational identity; psychometric evaluation; confirmatory factor analysis; measurement invariance